Symposium on the economic returns to education - Walsh, Brendan M. (Statistical and Social Inquiry Society of Ireland, 1998)
In my contribution to this Symposium I wish to explore two main themes. The first deals with the contribution of education to economic growth at the macro level. In this part I shall discuss the evidence of the importance of education ? or human capital formation ? as a determinant of the cross-country differences in living standards and rates of economic growth. The second topic I wish to develop is the measurement of the return to education at the level of the individual. In my review of both themes I shall refer to the policy implications and show how Ireland relates to the international experience.
Read before the Society, 19 February 1998
Keywords: Education; Returns to education; Human capital; Economic growth; 314.15